1976
DOI: 10.1073/pnas.73.10.3685
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental ascorbate in the supportive treatment of cancer: Prolongation of survival times in terminal human cancer.

Abstract: Ascorbic acid metabolism is associated with a number of mechanisms known to be involved in host resistance to malignant disease. Cancer patients are significantly depleted of ascorbic acid, and in our opinion this demonstrable biochemical characteristic indicates a substantially increased requirement and utilization of this substance to potentiate these various host resistance factors.The results of a clinical trial are presented in which 100 terminal cancer patients were given supplemental ascorbate as part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
416
0
12

Year Published

1979
1979
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(433 citation statements)
references
References 5 publications
5
416
0
12
Order By: Relevance
“…It was demonstrated by Cameron et al [133][134][135], that high-dose vitamin C improved the survival of patients with terminal cancer. However, the first documented study in which vitamin C was administered to cancer patients was carried out in the 1970s, by Pauling and Cameron.…”
Section: Vitamin C and Cancermentioning
confidence: 99%
“…It was demonstrated by Cameron et al [133][134][135], that high-dose vitamin C improved the survival of patients with terminal cancer. However, the first documented study in which vitamin C was administered to cancer patients was carried out in the 1970s, by Pauling and Cameron.…”
Section: Vitamin C and Cancermentioning
confidence: 99%
“…Clarifying the effects of Vc on human health is important because large doses are consumed (orally) by countless individuals worldwide without prescription and administered (most frequently intravenously) by thousands of alternative practitioners to patients with advanced cancer (52). The controversy regarding Vc and human health started in the 1970s with the debated anticancer claims by Pauling and Cameron (17)(18)(19)(20). More recent studies have demonstrated that a possible reason for the discrepancies between independent reports is the route of administration (oral plus intravenous versus oral only) (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Pauling asserted that megadose Vc could combat a wide range of human diseases, in particular cancer (16). He and Cameron performed clinical trials showing a significant efficacy of intravenous Vc in delaying the death of patients with terminal cancer (17,18). However, these results were heavily criticized after subsequent studies in the Mayo Clinic failed to reproduce this outcome with oral administration (19,20).…”
Section: Vcmentioning
confidence: 99%
“…Many patients were given 10 g daily orally, but a variety of other AA treatments were used. Copyright 1976 National Academy of Sciences, USA [4]. Relationship of dose of AA to total urinary excretion.…”
Section: Introductionmentioning
confidence: 99%